Political and Cultural Development in Albania Under Globalization Influences - Dumi, Alba; Rapushi, Bledar; Kuka, Lidra (Mediterranean Journal of Social Sciences, 2012)
The cultural development and Balkan universalism tries to arrive to an ideal of a borderless world of tolerance. Globalizationwill construct a unique culture identity that will represent the human gender. Another variant of this way of thinking is that Globalizationwill construct an environment in which culturally self-defining communities will coexist in an harmonious way. The Socio Evolutionism inBalkan countries approach of global transition (having Spencer, {Spencer ideas of globalization countries, year 2002} as its mainexponent and representative) occurred from mid nineteenth to mid twentieth century. During those times, socio evolutionism became theway in which human progress was normally conceptualized. Spencer ideas were not friendly with the concept of the State. This conceptis very wide when the Globalization is one impact that is now present for developing on Balkan areas. On matters of publicadministration, the Albania Government's strategy focused on addressing two inter-related sets of interventions: (a) strengthening publicfinancial management, including the management of both public expenditures and revenues; and (b) strengthening human resourcemanagement. The Albania Government worked with donors on the public financial management agenda by strengthening core publicfinancial management units (Ministry of Finance, Supreme Audit Institute, Procurement Directorate within the Office of the PrimeMinister) as well as the financial management units within each line agency (e.g., budget departments within line Ministries). On mattersrelating to public sector human resource management, the reform strategy envisaged addressing this issue in two major stages: civilservice reform and broader public sector human resource management reform. During the stage, the reforms aimed to create themanagerial and professional nucleus required to lead any serious efforts to improve the accountability and performance of publicinstitutions.